LINGUISTICS AND LAND RIGHTS - John David (Al-Qanṭara, 2022)
Abstract This paper surveys the various points at which linguistically informed judgements bear on issues in the operation of the land rights legislation in the N.T. The operation of the Aboriginal Land Rights (N.T.) Act 1976 has involved a lot of talk about Aboriginal land in Australia's Northern Territory (N.T.). The term "traditional owner", defined in the Act, has become a common expression. It refers to an Aboriginal person as owner of land according to Aboriginal tradition. The Act uses the term in the context of a traditional land claim, the running of a Land Council1, or the composition and affairs of an Aboriginal Land Trust. The concept is also relevant to complementary N.T. laws, such as those about sacred sites and sacred objects. An alternate term, common in the Top End of the N.T., is "custodian".